2015 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2015
DOI: 10.1109/iros.2015.7354053
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal collision avoidance for quadrotors using on-board visual detection

Abstract: Abstract-In this paper we present a collision avoidance system based on visual detection. Our hardware consists of a Hummingbird quadrotor equipped with a large red marker with two built-in fish-eye cameras. Fusion of the measurements from the two cameras is done using a Gaussian-mixture probability hypothesis density filter, which allows for tracking several aircrafts at the same time. Our collision avoidance algorithm is based on navigation functions designed to cope with cameras characterized by limited fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
3

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…Current implementations generally adopt mounted visual aids in the form of: colored balls (Roelofsen et al 2015), tags (Conroy et al 2014), or markers (Nägeli et al 2014). However, experiments during exploratory phases of this study have shown that the use of vision without such aids, for very small drones, and at low resolution [128 px × 96 px, as seen on a Lisa-S Ladybird (McGuire et al 2016)], is prone to either false positives or false negatives.…”
Section: Related Work and Research Contextmentioning
confidence: 93%
“…Current implementations generally adopt mounted visual aids in the form of: colored balls (Roelofsen et al 2015), tags (Conroy et al 2014), or markers (Nägeli et al 2014). However, experiments during exploratory phases of this study have shown that the use of vision without such aids, for very small drones, and at low resolution [128 px × 96 px, as seen on a Lisa-S Ladybird (McGuire et al 2016)], is prone to either false positives or false negatives.…”
Section: Related Work and Research Contextmentioning
confidence: 93%
“…In other words, none of these works explicitly addresses the FOV problem. Our previous work [12] is, to our knowledge, the first collision algorithm that takes into account the FOV limitations and has been experimentally validated [13].…”
Section: Introductionmentioning
confidence: 99%
“…5. The implementation of the camera sensor model is similar to [19], which uses the standard camera with distortion model, with the exception of the measurement model for the apparent width w…”
Section: (I)mentioning
confidence: 99%
“…For this reason, the state estimation in this framework is performed with a Gaussian-Mixture Probability Hypothesis Density filter (GM-PHD) described in [18]. The GM-PHD filter is a multitarget tracker that has been successfully applied to markerbased single-camera multi-target tracking in previous work [19]. In this paper, we apply the same methodology to the more general problem of marker-less multi-target tracking.…”
Section: Introductionmentioning
confidence: 99%